The Nexus between risk and bank stability in the Indonesian Islamic Rural Bank - Hendri, Zul; Arshad, Noraziah Che; Rahmany, Sri; Wiharto, Slamet; Sintarini, Fitriasari (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study examines the relationship between bank risk and stability in the case of the Islamic Rural Bank (IRB) of Indonesia.Methodology – This study analyzes 154 Islamic Rural Banks (IRBs) from 2015 to 2023 using quarterly data. It employs a static panel data regression with unbalanced data. The final regression model was selected using the F-test, LM test, and Hausman test to compare the common, fixed, and random effect methods.Findings – Liquidity and financing risks have a negative relationship with IRB stability. The negative impact of financing risk on IRB stability decreased during Covid-19. The negative effects of liquidity risk on IRBs' stability of IRBs increased for IRBs on Java. In contrast, the negative impact of financing risk on stability decreased for IRB located in and outside Java.Implications – First, IRB must effectively manage their liquidity risk to maintain bank stability. Second, IRBs must reduce non-performing financing (NPF) to encourage bank stability. Third, banks’ operational and capital efficiencies must be improved.Originality – This study aims to fill the existing research gap by analyzing the effect of liquidity and financing risks on the stability of the Islamic Rural Bank as a small Islamic bank. Furthermore, this study includes the Covid-19 variable as a moderating variable that affects the effect of liquidity and financing risks on IRB stability.